Colonization of Table Grape Bunches by Alternaria alternata and Rot of Cold-Stored Grapes - Swart, A.E.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
Assessment of latent Alternaria alternata infections in table grapes indicated that infections occurred in commercial vineyards during the entire period of bunch development. Mature bunches were asymptomatic despite high levels of A. alternata recovered from triple-sterilized bunch tissue.  Inoculation studies showed no shift in disease susceptibility of ripening grape berries, and postharvest rot was not related to the level of natural infection. Late season fungicidal sprays, or dip treatments that ensured better penetration and coverage of inner parts, resulted in no meaningful reduction in postharvest rot. Based on the behaviour of the pathogen, it is suggested that additional fungicide programmes for the control of the disease should not be followed in commercial vineyards. Instead, attention should be given to physiological and stress factors, such as mechanical and sulphur dioxide damage that might predispose cold-stored bunches to A. alternata decay.